O amor e a cura da alma em Platão e Jung - Mandai, Sarah Sumiê Rocha (2018)
This dissertation seeks to determine the relationship between love and soul health, in Plato's philosophy and in Jung's psychology. In both authors, psychology and ethics are inseparable. In Plato, love as the soul's impulse to the Good grounds the health and happiness of the soul. In the same way, the psychic energy in its transference from the biological to the cultural, runs through the ethical conflicts that determine psychological health. From this, the presence of analogies between Plato's soul and the psychic apparatus of modern psychology, and between the function of Eros and Psychic Energy, was observed. Another analogy pointed out by Jung himself is between the Platonic Ideas and the Archetypes. This theoretical convergence endorses the understanding that love participates in the mental mechanics as an essential part of the manifestation and maintenance of life and health. Moreover, the therapy resulting from this interaction does not escape the proximity between self-knowledge and analysis.